The effectiveness of teaching sexual education component to mothers on anxiety fifth and sixth grade girls shahre ghods - samira tavoosi; Abdollah Shafiabadi; Hosein Salimi Bajestani (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2020)
This study has been aimed to evaluate the effectiveness of sexual education component to the mother's on anxiety the fifth and sixth grade girls. Research method was Quasi-experimental study with pretest – posttest and control group. The study population included all fifth and sixth grade girls in the Ghods city have formed the 93-94 school year. Research tool was Spielberger's State-Trait Anxiety Inventory. Research sample have been 30 primary school students Ghods city who were selected randomly Cluster. And then randomly divided into control and experimental groups.at first all of subjects were pre-test. At fallowing the mothers of students in the experimental group received six sessions of sexual education component and at the end post-test was taken from sample group. Results analyzed using ANCOVA represents the difference between the two groups was 99% sure. The average modified Anxiety variable in experimental group was 67/64 and 66/89 in the control group that indicating less anxiety in the experimental group. The average modified trait Anxiety variable in the experimental group were 68/33 and 18/44 in the control group. The average modified state Anxiety variable in the experimental group were 31/08 and the control group 38/45 that showed trait and state anxiety decreased in the experimental group. So in this study, the researchers came to the conclusion that teaching sexual education component to mothers in reducing anxiety of girls has been effective.